The Impactfulness of the Teaching Games for Understanding (TGFU) Model in Improving Physical Education Student Achievement: A Systematic Literature Review - Abiansyah Budiman; Yogi Akin; Sucipto Sucipto (Universitas Tadulako, 2025)
Physical education classroom activities are often dominated by technical skill drills rather than emphasizing game intelligence, engagement, and meaningful classroom activity experiences. In recent years, the Teaching Games for Understanding (TGfU) model has gained increasing attention as an alternative pedagogical approach in physical education. However, findings on its effectiveness remain fragmented across studies and often focus on limited classroom activity outcomes or specific sport contexts. Therefore, this study aims to systematically examine the effects of the Teaching Games for Understanding (TGfU) classroom activity model on student achievement in physical education by synthesizing empirical evidence published between 2018 and 2024. This study employed a Systematic Literature Review (SLR) approach using PRISMA guidelines to systematically identify, screen, and analyze relevant literature. A total of 15 articles met the inclusion criteria and were included in the review. The findings indicate that the TGfU model positively influences student achievement, fundamental sports skills, classroom activity motivation, active classroom activity time, and social interaction in physical education classes. In addition, TGfU supports students' cognitive and social development through game-based classroom activities that encourage decision-making, collaboration, and problem-solving. These findings confirm that TGfU is an effective and relevant student-centered learning model for contemporary physical education. Furthermore, future research is recommended to employ longitudinal and experimental research designs involving larger and more diverse samples to strengthen evidence regarding the long-term effectiveness of TGfU implementation across various educational contexts.